Correlation of clinicopathologic features and lung squamous cell carcinoma subtypes according to the 2015 WHO classification. Issue 12 (December 2017) - Chen, Rongrong; Ding, Zhengping; Zhu, Lei; Lu, Shun; Yu, Yongfeng
Abstract: Aims: This study aimed to determine the relationship between clinicopathologic features and lung squamous cell carcinoma (LSCC) subtypes according to the 2015 WHO classification. Methods: We identified 824 operable LSCC patients undergoing a complete surgical resection at Shanghai Chest Hospital between April 2015 and January 2017. Immunohistochemistry was used to investigate the clinicopathologic features. Results: Among them, the percentages of LSCC subtypes were 66.1% (545/824), 28.6% (236/824), and 5.2% (43/824) for keratinizing squamous cell carcinoma (KSCC), nonkeratinizing squamous cell carcinoma (NKSCC), and basaloid squamous cell carcinoma (BSCC), respectively. There were more males, more smokers, and more pneumonectomy surgeries in KSCC patients (p = 0.008, p = 0.000, p = 0.043). There were more N2 lymph node involvement and pathological stage III in NKSCC patients (p = 0.01, p = 0.03). BSCC did not demonstrate specificity to anything, but expressed adenocarcinoma markers more frequently. No significant difference existed between pathological subtypes and other clinicopathologic features, such as age, location type, visceral pleural involvement and lymphovascular invasion. The frequencies of EGFR sensitive mutations and ALK rearrangements were not significantly different among three subtypes. Conclusion: Significant relationships exist between some clinicopathologic features and LSCC subtypes.